Participation in a 20‐Year Randomized Dietary Trial and University Enrollment - Viinikainen, Jutta; Heineck, Guido; Böckerman, Petri; Pahkala, Katja; Jula, Antti; Kari, Jaana T.; Lagström, Hanna; Niinikoski, Harri; Pehkonen, Jaakko; Rovio, Suvi P.; Rönnemaa, Tapani; Salo, Pia; et al. (Wiley, 2026)
Background and Aims
A nutritionally balanced, age-appropriate diet is crucial for child development. The randomized Special Turku Coronary Risk Factor Intervention Project (STRIP) was a 20-year dietary intervention starting at 7 months of age. It aimed at improving fat quality and promoting healthy foods to prevent cardiovascular diseases. We examined whether the intervention was associated with university enrollment and difficulties in school-related tasks in a post hoc setting.
Methods
Participants (n = 1062) were recruited at the age of 5 months between December 1, 1989, and May 30, 1992, from child health clinics in Turku, Finland, and were randomly assigned to either the intervention (n = 541) or control group (n = 521) at the age of 7 months. Children in the intervention group received personalized dietary counseling through age 20, without a fixed diet. We used linear probability models estimated by ordinary least squares (OLS) to investigate whether being in the intervention group was associated with university enrollment by age 26, and OLS regressions to examine its association with difficulties in school-related tasks at age 10. The study is reported in accordance with the CONSORT guidelines.
Results
In total, 639 participants provided university enrollment data. Among males from low-education families, being in the intervention group was associated with a 32 percentage point higher likelihood of enrollment (b = 0.324, p = 0.004, 95% confidence interval (CI): 0.103, 0.546). Among all males the association was 11 percentage points (b = 0.107, p = 0.07, 95% CI: −0.007, 0.220), and among females −3 percentage points (b = −0.033, p = 0.53, 95% CI: −0.137, 0.071). The results also suggested that diet, rather than cardiovascular health, may serve as a mediator.
Conclusions
Long-term dietary counseling is associated with increased educational attainment among males from low-education families. The study is registered at ClinicalTrials.gov (#NCT00223600).